MORPHOMETRIC CHARACTERISTICS OF THE MELISSA RIVER MICRO-WATERSHED AND ESTIMATION OF NITROGEN ANS PHOSPHORUS INPUTS FROM FISH FARMNING PONDS - Panzera, Nicole; Araújo, Analice Timoteo; Werneck, Pedro Rondon; Feiden, Aldi (Seven Editora, 2025)
Advances in geotechnology have increased the accuracy of environmental monitoring, making remote sensing essential for watershed management. This study analyzed the Melissa River microbasin, a tributary of the Piquiri River (western Paraná), to characterize morphometric aspects, map excavated ponds, and estimate nutrient input from fish farming. The basin was delimited using Digital Elevation Model (30 m) images processed in QGIS 3.22.14 and GRASS GIS, generating maps of slope, hypsometry, soils, and land use. The morphometric analysis included eight indices, and the pond mapping used Google Earth® imagery. The microbasin has flat to gently undulating relief, with altitudes ranging from 220 to 820 m, with a predominance of 520–720 m (72.26%). The soils are predominantly RED LATOSOL (75%), followed by RED NITOSOL (19.46%), suitable for fish farming due to their impermeability. Land use is dominated by soybeans (63.65%), followed by forests (15.65%). The indices (Kc=2.73; Dd=0.89) indicate an elongated shape, low runoff, and low flood risk. A total of 278 ponds were identified, 70.86% of which were class I, but class III ponds accounted for 52.60% of the water table. The estimated production was 4,373 t, with 199.66 t of nutrients contributed by breeding and 8.51 t by harvesting. It is concluded that the microbasin presents favorable conditions for aquaculture, but larger ponds require management to reduce eutrophication, highlighting the importance of geotechnologies in water management.DOI: https://doi.org/10.56238/sevened2025.029-071